Barriers to recycling plastics from the perspectives of industry stakeholders: a qualitative study. Issue 1 (31st December 2023) - Roy, Deborah; Berry, Emma; Orr, Karen; Dempster, Martin
ABSTRACT: Previous research exploring the psychological, social, and environmental barriers to recycling has predominantly focused on consumer attitude and behaviour. However, the plastic system involves a chain of stakeholders with a role in decision-making and actions in relation to plastic production and management post-use, affirming the need to explore the barriers to recycle across various other stakeholders implicated in the lifecycle of plastic product and packaging. To expand this evidence-base, N = 12 in-depth qualitative semi-structured interviews explored the perspectives of some of the stakeholders responsible for various aspects of the plastic life cycle (fast moving consumer goods industry, retailers, and waste management professionals). Using a semi-directed content analysis approach via NVivo, three overarching themes were extracted from the data: 1) Disempowerment and lost opportunities 2) Solutions and opportunities reside with use of legislation 3) The circular economy stakeholders need motivation, and to be more knowledgeable. The themes suggest that stakeholders implicated in the plastic lifecycle lack the drive and perceived personal and organizational efficacy to generate meaningful change in the plastic system. These barriers are exacerbated by a lack of collegial partnerships between stakeholders to facilitate knowledge transfer and collective action. This study recommends greater collaboration and communication between stakeholders implicated in the end-to-end plastic "chain", and makes a renewed call for further legislation, having shed light on important socio-political and pragmatic barriers to reducing plastic waste.